The crosses of Pompeii : Jesus-devotion in a Vesuvian town - Longenecker, Bruce W. (Fortress Press, 2016)
The eruption that destroyed Pompeii in 79 preserved a wealth of evidence about the town, buried for centuries in volcanic ash. Since the town's excavations in the eighteenth century, archaeologists have disputed the evidence that might attest the presence of Christians in Pompeii before the eruption. Now, Bruce Longenecker reviews that material evidence and introduces artifacts previously unrecognized for their relevance to the issue. Illustrated with maps, charts, photographs, and line drawings depicting artifacts from the town, The Crosses of Pompeii presents an elegant case for the presence of Jesus-devotion in the Vesuvian town. Longenecker's arguments require dramatic changes to our understanding of the history of earliest Christianity.